Analysis Of The Leading Sector Of Ambon City During The Covid-19 Pandemic - Wirawan, Dandy Ananda Patria (Politeknik Keuangan Negara STAN, 2023)
Gross Regional Domestic Product (GDP) is a major factor in viewing economic growth in a region. High production will contribute to Regional Original Income (PAD), which can later be used by regions to build infrastructure and other regional needs. However, the COVID-19 pandemic that has hit Indonesia has hampered the economy. This condition also hit Ambon City which is the capital of Maluku Province. The COVID-19 pandemic has had a different impact on every business sector in Ambon City. Through analysis of Location Quotient (LQ), Dynamic Location Quotient (DLQ), and Shift-share, also supported by using overlay identification analysis, conclusions were drawn when entering the COVID-19 pandemic, the period 2016 to 2020, the leading sector in Ambon City was the Financial Services and Insurance as well as Government Administration, Defense, and Compulsory Social Security sectors.